Lack of acclimatization to chronic hypoxia in humans in the Antarctica. Issue 1 (December 2017) - Porcelli, Simone; Marzorati, Mauro; Healey, Beth; Terraneo, Laura; Vezzoli, Alessandra; Bella, Silvia; Dicasillati, Roberto; Samaja, Michele
Abstract The study was carried out at Concordia Station (Antarctic Plateau). The aim was to investigate the respiratory and haematological responses to hypoxia in healthy subjects living at constant altitude. Thirteen men and women (34.1 ± 3.1 years) were exposed for 10 months to hypobaric hypoxia (oxygen level equivalent to 3800 m asl). These unique conditions enable a greater accuracy of monitoring human responses to chronic hypoxia than can be achieved elsewhere. Blood haemoglobin and erythropoietin concentrations were determined at sea level (Pre), and after 3, 7, 20, 90 and 300 days at altitude. Blood gas analysis, base excess and arterial oxygen saturation were measured at Pre, and after 150 and 300 days at altitude. Erythropoietin returned quickly to baseline level after a transient increase in the first days. Blood haemoglobin concentration started increasing at day 7 and remained markedly higher for the entire duration of the mission. At day 150 the blood carbon dioxide partial pressure was markedly reduced, and consequently blood pH remained higher at negative base excess until day 300. The arterial oxygen saturation remained lower than Pre throughout. In conclusion, humans display little capacity of hypoxia acclimatization even after ten months of constant exposure to low oxygen partial pressure.